The politics of children's inclusion in Finnish music schools - Tuovinen, Tuulia (Taideyliopiston Sibelius-Akatemia, 2026)
The paradigmatic shift toward participatory governance in contemporary policy making has established public engagement as a fundamental principle of national strategies and policy frameworks across diverse contexts. Despite this strong national commitment to democratic values and participatory principles, children and young people are however frequently excluded from collaborative partner status in policy processes. This exclusion constitutes a critical contradiction between stated democratic principles and actual participatory practice within educational governance, where processes such as the national curriculum development are framed as collaborative efforts between the public administration and various stakeholders. This study addresses the identified disjuncture between policy aspirations and their practical realization by exploring children’s inclusion and policy co-construction in music school education as part of Basic Arts Education in Finland. Situated within the multidisciplinary field of child perspectives studies, this practitioner-inquiry employs methodological approaches from developmental work research and cultural-historical activity theory. Three central questions guided the research: How do children and young people co-construct music school practices when their agency and decision-making are supported by their teacher? What institutional dynamics and democratic possibilities emerge within such co-constructed policy processes? How does the co-construction of music school practices with students contribute to broader understandings of participatory governance and inclusion in music education? The study's empirical material comprises multiple data sources generated during a twelve-month formative intervention conducted in two music schools. The intervention involved 25 music school students (ages 9–15) who planned and implemented their own projects in peer groups under the practitioner-researcher’s guidance. Video recordings of group lessons were supplemented by student interviews, student-teacher conversations conducted through a messaging application (WhatsApp), and a practitioner-researcher diary of the intervention process. The study incorporated music school policy review, including examination of national curricular frameworks and assessments. The analysis involved several iterative steps using diffractive methodology. Ethical protocols included securing informed consent from guardians and participating students. The findings indicate that children's inclusion in music schools can be enhanced by supporting their agency through experiences of relevance, social connectedness, and ability to act. This requires attention to both individual skill development and horizontal and socio-spatial relationships within students' music-making, as their aspirations and agentic orientations are constituted through relational processes. Students' opportunities to influence significant matters revealed how individual needs are interconnected with social relationships, with music-focused classes providing important peer networks and social support. The analysis showed that enhancing inclusion requires not merely addressing access and representation but also reimagining the various conceptualizations and frameworks through which children and their musical learning are understood, managed, and administered. While music schools' historical mandates and institutional affiliations have reinforced linear progression expectations, structured according to professional study requirements, this study contends that policies formulated and enacted without children's direct participatory engagement render their experiences of inclusion increasingly arbitrary. Understanding student agency as an ecological achievement necessitates fundamental theoretical and practical reconsideration of how musical development is understood and facilitated in music education. As a whole, the study suggests that allowing children and young people to bring their perspectives to music education can restore art’s meaning-making capacity to fundamental questions of human and social existence.

Osallistava hallinto ja julkisten palvelujen yhteiskehittäminen ovat vakiinnuttaneet kansalaisten osallistumisen kansallisten strategioiden ja politiikkikehysten lähtökohdaksi moninaisissa konteksteissa. Huolimatta vahvasta kansallisesta sitoutumisesta demokraattisiin arvoihin ja osallistumisen periaatteisiin, lapset ja nuoret jäävät Suomessa usein ilman asemaa tasavertaisina yhteistyökumppaneina politiikkaprosesseissa. Tämä poissulkeminen muodostaa merkittävän ristiriidan julkilausuttujen demokraattisten periaatteiden ja niiden käytännön toteutumisen välillä myös koulutuksen hallinnossa, jossa esimerkiksi opetussuunnitelman perusteiden laatimisen kuitenkin nähdään perustuvan julkishallinnon ja eri sidosryhmien väliseen yhteistyöhön. Tämä tutkimus vastaa tähän haasteeseen koulutuspoliittisten tavoitteiden käytännön toteutumisessa tarkastelemalla lasten osallisuutta ja julkisten palvelujen yhteiskehittämistä osana taiteen perusopetuksen musiikkioppilaitoksia. Lapsinäkökulmaisen tutkimuksen monitieteiseen kenttään sijoittuva opettajatutkimus hyödyntää metodologisia lähestymistapoja kehittävästä työntutkimuksesta ja kulttuurihistoriallisesta toiminnan teoriasta. Tutkimusta ohjasivat kolme keskeistä kysymystä: Miten lapset ja nuoret yhteiskehittävät musiikkiopistokäytäntöjä silloin, kun opettaja tukee heidän toimijuuttaan ja päätöksentekoaan? Millaisia institutionaalisia dynamiikkoja ja demokraattisia mahdollisuuksia yhteiskehitetyissä politiikkaprosesseissa syntyy? Millä tavoin oppilaiden kanssa toteutettu musiikkiopiston käytäntöjen yhteiskehittäminen voi edistää laajempaa ymmärrystä osallistavasta hallinnosta ja osallisuudesta musiikkikasvatuksessa? Tutkimuksen empiirinen aineisto koostuu videoiduista ryhmätunneista osana formatiivista interventiota, jossa 25 musiikkiopisto-oppilasta (ikäjakauma 9–15-vuotta) suunnittelivat ja toteuttivat omia projektejaan vertaisryhmissä opettajatutkijan ohjauksessa. Interventio toteutettiin kahdessa musiikkioppilaitoksessa kahdentoista kuukauden aikana. Ryhmätuntien videotallenteita täydennettiin oppilashaastatteluilla, oppilaiden ja opettajan välisillä keskusteluilla viestintäsovelluksessa (WhatsApp), sekä opettajatutkijan tutkimuspäiväkirjalla. Tutkimuksessa tarkasteltiin myös musiikkiopiston ohjausjärjestelmää kansallisten opetussuunnitelman perusteiden ja valtakunnallisten arviointien kautta. Analyysi toteutettiin useiden iteratiivisten vaiheiden kautta diffraktiivista metodologiaa hyödyntäen. Tutkimuseettisten periaatteiden mukaisesti tutkimukseen osallistumisesta varmistettiin suostumus huoltajilta ja oppilailta. Tutkimustulokset osoittavat, että lasten osallisuutta musiikkiopistoissa voidaan vahvistaa tukemalla heidän toimijuuttaan merkityksellisyyden, sosiaalisen yhteenkuuluvuuden ja pystyvyyden kokemusten kautta. Tämä edellyttää huomion kiinnittämistä yksilölliseen taitojen kehittämiseen sekä oppilaiden välisiin horisontaalisiin ja sosio-spatiaalisiin suhteisiin musiikin tekemisessä. Oppilaiden mahdollisuudet vaikuttaa heille merkityksellisiin asioihin toivat esiin sen, kuinka yksilölliset tarpeet kietoutuvat sosiaalisiin suhteisiin. Musiikkipainotteiset luokat tarjosivat oppilaille tärkeitä vertaisverkostoja ja sosiaalista tukea. Tutkimus osoittaa, että osallisuuden edistäminen edellyttää julkisten palvelujen saatavuuden ja lasten päätöksentekoon osallistumisen lisäksi myös lapsiin ja heidän musiikilliseen oppimiseensa liitettyjen käsitysten ja kehysten uudelleentarkastelua. Vaikka musiikkiopistojen historialliset tehtävät ja institutionaaliset sidonnaisuudet ovat muodostaneet musiikkiopisto-opintoihin lineaarisen etenemisen odotuksia ammattiopintojen vaatimusten näkökulmasta, tämä tutkimus esittää, että ilman lasten suoraa osallistumista laaditut ja toteutetut politiikat tekevät heidän osallisuuden kokemuksistaan sattumanvaraisia. Lasten toimijuuden ymmärtäminen osana erilaisia suhteita edellyttää myös musiikillisen kehityksen uudelleen tarkastelua. Kokonaisuutena tutkimus esittää, että lasten kanssa toimimalla ja heidän näkökulmiaan ymmärtämällä on mahdollista palauttaa taiteen merkityksenantoja inhimillisen olemassaolon peruskysymyksiin.
Keywords: julkinen politiikka; musiikkiopistot; yhteiskehittäminen; co-construction; public policy; demokratia; kehittävä työntutkimus; lapset (ikäryhmät); musiikkioppilaitokset; osallisuus; taiteen perusopetus; yhteissuunnittelu; basic education in the arts; children (age groups); democracy; developmental work research; inclusion; music schools; MuTri